“This Silence is like an Invisible Wall that Needs to be Shattered and Broken”. An Interview with Jupiter Child: “This Silence is like an Invisible Wall that Needs to be Shattered and Broken”. An Interview with Jupiter Child - Marronage (Periskop – Forum for kunsthistorisk debat, 2021)
“This Silence is like an Invisible Wall that Needs to be Shattered and Broken”. An Interview with Jupiter Child